1998
DOI: 10.4141/p97-071
|View full text |Cite
|
Sign up to set email alerts
|

Nectar quality in open-pollinated, pol CMS hybrid, and dominant SI hybrid oilseed summer rape

Abstract: . Nectar quality in open-pollinated, pol CMS hybrid, and dominant SI hybrid oilseed summer rape. Can. J. Plant Sci. 78: 79-89. Nectar sugar composition and temporal patterns of nectar sugar production were examined in oilseed summer rape (Brassica napus L. ssp. oleifera (Metzg.)) from six open-pollinated, eight pol cytoplasmic male-sterile (CMS) hybrid and seven dominant self-incompatible (SI) hybrid cultivars at three field plot sites in Manitoba. The total sugar content of nectar samples was measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…Nectar was then allowed to accumulate in these flowers for 24 h, prior to being sampled to measure 24-h secretion rate. To control for potential diel patterns of nectar production within flowers (Pernal & Currie, 1998), all plants that were flowering within a block were sampled during a defined, 1-h period (Table S1). As plants started flowering on different days, nectar samples were collected over multiple days (Table S2).…”
Section: Nectar Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nectar was then allowed to accumulate in these flowers for 24 h, prior to being sampled to measure 24-h secretion rate. To control for potential diel patterns of nectar production within flowers (Pernal & Currie, 1998), all plants that were flowering within a block were sampled during a defined, 1-h period (Table S1). As plants started flowering on different days, nectar samples were collected over multiple days (Table S2).…”
Section: Nectar Collection and Analysismentioning
confidence: 99%
“…Oilseed rape breeding programmes have conserved the function of nectar production in varieties (Pernal & Currie, 1998;Pierre et al, 1999), but little is known about the production of nectar in the three breeding systems. There is limited evidence that Ogura cytoplasm used in CMS hybrids may result in less developed nectaries with associated lowered nectar production (Pelletier et al, 1987;Mesquida et al, 1991), but Pierre et al (1999) found no differences between the nectar volumes and sugar concentrations between three Ogura CMS hybrids and three OP varieties.…”
Section: Introductionmentioning
confidence: 99%
“…In our study of annual caraway (var. There is indirect evidence from indeterminate-flowering, non-apiaceaen species (Andrejeff, 1932;Fahn, 1949;Pernal and Currie, 1998) to support the hypothesis that nectar sugar yields in later flowers are reduced by sparser resources. Under these conditions, seed set in this self-compatible species was low (Ͻ10%), in accordance with a previous study (0-12%;Németh, Bernáth, and Petheô, 1999), and it would be interesting to determine whether or not maternal resources are adequate (Stephenson, 1981) to allow higher umbel orders to produce as much nectar when lower orders had previously been pollinated and commenced seed filling.…”
Section: Floral Nectar Yields Among Umbel Orders and Individual Plants-mentioning
confidence: 99%
“…Under these conditions, seed set in this self-compatible species was low (Ͻ10%), in accordance with a previous study (0-12%;Németh, Bernáth, and Petheô, 1999), and it would be interesting to determine whether or not maternal resources are adequate (Stephenson, 1981) to allow higher umbel orders to produce as much nectar when lower orders had previously been pollinated and commenced seed filling. There is indirect evidence from indeterminate-flowering, non-apiaceaen species (Andrejeff, 1932;Fahn, 1949;Pernal and Currie, 1998) to support the hypothesis that nectar sugar yields in later flowers are reduced by sparser resources. Similarly, a relationship between low seed set and surplus of photosynthate in nectar had been postulated for Daucus carota (Erickson, Peterson, and Werner, 1979).…”
Section: Floral Nectar Yields Among Umbel Orders and Individual Plants-mentioning
confidence: 99%
“…Bumble bees may not be ideal pollinators for hybrid oilseed rape production because they often restrict their foraging to the collection of nectar only (Pyke 1982 and references therein). Although Oguru male-sterile hybrid oilseed rape flowers may have greatly decreased levels of nectar compared with pollen parent flowers (Mesquida and Renard 1979a,b;Pierre et al 1999), recent research found the production and quality of nectar sugar in Polima oilseed rape hybrids to be similar to those of open-pollinated varieties (Pernal and Currie 1997). Our yield data from 1994 (Table 6) and the fact that the bumble bee colonies increased over the summer indicate that R-lines were well visited by bumble bees.…”
Section: Discussionmentioning
confidence: 99%